Clausena harmandiana root extract ameliorates Aβ1-42 induced cognitive deficits, oxidative stress, and apoptosis in rats - Wanassanun Pannangrong; Nutchareeporn Nillert; Chantana Boonyarat; Jariya Umka Welbat; Supataechasit Yannasithinon; Pannawat Choowong-In (BMC, 2024)
Abstract Background Clausena harmandiana (CH), commonly known as song fa dong, was a medicinal plant traditionally used to treat illnesses and as a health tonic. CH root extract (CHRE) exhibited various bioactivities, including neuroprotective, antioxidant, antimicrobial, antifungal, anti-inflammatory, and anti-cancer effects. However, CHRE data on neuroprotective in AD-like animal models were still scarce. Objectives This study aimed to investigate the effects of CHRE on Aβ1-42-induced cognitive deficits, free radical damage, and neuronal death in rats. Methods Forty-eight adult male Sprague-Dawley rats (250-300 g) were classified as sham control (SC), V+Aβ, Vit C+Aβ, CHRE125+Aβ, CHRE250+Aβ, and CHRE500+Aβ (n = 8 in each group). Animals were orally administered with 0.5% sodium carboxymethylcellulose, vitamin C (200 mg/kg BW), or CHRE (125, 250, and 500 mg/kg BW) and were untreated for 35 days. On day 21, all treated rats were injected with 1 µl of aggregated Aβ1-42 (1 µg/µl) into the lateral ventricles, bilaterally, whereas untreated rats were injected with sterilized normal saline (NS). The Morris water maze test estimated the rat's learning and memory one week later. At the end of the treatment, all rats were sacrificed, and their brains were removed and divided into two hemispheres. On the left, morphological changes and neuronal density were observed in hippocampal CA1 and CA3 regions. While, on the right, changes in free radical damage markers (SOD, CAT, GPx, MDA, and Nrf2) and protein expression of active caspase-3 were evaluated in the hippocampus. Results Pretreatment with CHRE at all doses could alleviate spatial learning and memory defects. CHRE also improved morphological changes and a decrease in neuronal density in CA1 and CA3 regions. Additionally, CHRE significantly increased the activities of antioxidant enzymes (SOD, CAT, GPx) and Nrf2 expression. This was coupled with significantly decreased MDA levels and active caspase-3 expression in the hippocampus of Aβ1-42-induced rats, which was similar to vitamin C exposure. Conclusions Our findings suggested that CHRE ameliorated cognitive deficits and exhibited neuroprotective effects by reducing free radical damage and mitigating neuronal abnormality and neuronal death.